1970
DOI: 10.3329/bjog.v23i2.4962
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomised Trial of Nifedipine Versus Placebo in Preterm Labour

Abstract: Introduction:Preterm labour is defined as the presence of uterine contractions of sufficient frequency and intensity to effect progressive effacement and dilatation prior to term gestation. Preterm labour and preterm births occur in approximately 12 % of all pregnancies and is the leading cause of neonatal death in the United States as well in the developing countries 1 . In addition, preterm birth accounts for 70% of neonatal morbidity, and mortality, and health care spent on the neonate 2 .Despite the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Of the two trials, the nonplacebo trial by Zhang, which included nifedipine maintenance tocolysis at two dosages compared with no treatment until 35 weeks of gestation, revealed a significant reduction in preterm birth before 37 weeks of gestation, 5,6 whereas the placebo-controlled trial by Ara failed to demonstrate a difference in preterm birth before 37 weeks. 5,7 Although not powered for neonatal outcomes, our second finding regarding neonatal outcomes comports with the ACOG statement that, although tocolysis may result in short-term pregnancy prolongation, there is no evidence that such therapy translates into significant neonatal benefit. 2 The report by Flenady, 5 which compared nifedipine with other tocolytics, found beta adrenergic-receptor agonists compared with nifedipine resulted in a reduction of short-term adverse neonatal outcomes but failed to affect perinatal mortality.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Of the two trials, the nonplacebo trial by Zhang, which included nifedipine maintenance tocolysis at two dosages compared with no treatment until 35 weeks of gestation, revealed a significant reduction in preterm birth before 37 weeks of gestation, 5,6 whereas the placebo-controlled trial by Ara failed to demonstrate a difference in preterm birth before 37 weeks. 5,7 Although not powered for neonatal outcomes, our second finding regarding neonatal outcomes comports with the ACOG statement that, although tocolysis may result in short-term pregnancy prolongation, there is no evidence that such therapy translates into significant neonatal benefit. 2 The report by Flenady, 5 which compared nifedipine with other tocolytics, found beta adrenergic-receptor agonists compared with nifedipine resulted in a reduction of short-term adverse neonatal outcomes but failed to affect perinatal mortality.…”
Section: Discussionmentioning
confidence: 79%
“…Of the two trials, the nonplacebo trial by Zhang, which included nifedipine maintenance tocolysis at two dosages compared with no treatment until 35 weeks of gestation, revealed a significant reduction in preterm birth before 37 weeks of gestation, 5,6 whereas the placebo-controlled trial by Ara failed to demonstrate a difference in preterm birth before 37 weeks. 5,7…”
Section: Discussionmentioning
confidence: 99%
“…The review included 38 trials of 3550 patients; nifedipine was assessed in 35 of these trials and nicardipine in three. In the two studies that compared nifedipine to placebo or no treatment, there was a delay in delivery and a reduction in birth less than 48 h after trial entry with nifedipine use (Zhang & Liu 2002, Ara & Banu 2008. This supports the use of nifedipine to prolong pregnancies in the short term, to provide time for corticosteroid administration and to transfer to higher level care.…”
Section: R13mentioning
confidence: 92%
“…However, in terms of the outcome of reducing the incidence of preterm birth, the two trials found conflicting results. The placebocontrolled trial showed nifedipine was no different to placebo (Ara & Banu 2008), while the non-placebo controlled trial showed nifedipine reduced the occurrence of preterm birth (Zhang & Liu 2002). These different findings may be attributable to the fundamental differences between the two trials, particularly regarding doses and blinding to the intervention.…”
Section: R13mentioning
confidence: 99%
“…Comparing calcium channel blockers (mainly nifedipine) with other tocolytics (betamimetics, nonsteroidal antiinflammatories, and oxytocin receptor antagonists), there was no significant reduction in delivery within 48 hours of treatment or perinatal mortality. 35 Due to substantial heterogeneity, outcome data for PTB < 37 weeks were not combined; one placebo-controlled trial showed no difference, 36 while the other (non-placebo-controlled trial) reported a reduction in PTB < 37 weeks (►Table 1). 37 Calcium channel blockers have a favorable side-effect profile when compared with the betamimetics, with the most common side effect being hypotension-related.…”
Section: Calcium Channel Blockersmentioning
confidence: 99%